2012
DOI: 10.1073/pnas.1213076110
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 suppresses RNA synthesis after UV irradiation in combined xeroderma pigmentosum group D/Cockayne syndrome (XP-D/CS) cells

Abstract: Specific mutations in the XPD subunit of transcription factor IIH result in combined xeroderma pigmentosum (XP)/Cockayne syndrome (CS), a severe DNA repair disorder characterized at the cellular level by a transcriptional arrest following UV irradiation. This transcriptional arrest has always been thought to be the result of faulty transcription-coupled repair. In the present study, we showed that, following UV irradiation, XP-D/CS cells displayed a gross transcriptional dysregulation compared with "pure" XP-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…This paper provided evidence that CSB and P53 play a reciprocal role in regulating the transcriptional program in response to UV, a concept that has been mechanistically investigated by Fan and colleagues [120, 121]. Also, Velez-Cruz et al [122] recently described a defect in reassembling gene promoters following UV exposure in cells from an XP-D/CS patient, but not in cells from a XP-D patent with pure XP, further supporting the concept of CS as a transcription disorder. Of more physiologic relevance to the internal manifestations of CS, CS cells have a defective response to hypoxia [94].…”
Section: A New Look At An Old Hypothesis: Cs As a Rnapi And Rnapiimentioning
confidence: 74%
“…This paper provided evidence that CSB and P53 play a reciprocal role in regulating the transcriptional program in response to UV, a concept that has been mechanistically investigated by Fan and colleagues [120, 121]. Also, Velez-Cruz et al [122] recently described a defect in reassembling gene promoters following UV exposure in cells from an XP-D/CS patient, but not in cells from a XP-D patent with pure XP, further supporting the concept of CS as a transcription disorder. Of more physiologic relevance to the internal manifestations of CS, CS cells have a defective response to hypoxia [94].…”
Section: A New Look At An Old Hypothesis: Cs As a Rnapi And Rnapiimentioning
confidence: 74%
“…We found that both WT XPG and an A792V mutant derived from an XP-G patient form stable complexes with TFIIH, allowing the phosphorylation and transactivation of nuclear receptors, whereas a mutant XPG harboring a C-terminal deletion (derived from an XP-G/CS patient) did not form a complex with TFIIH, resulting in reduced transactivation of nuclear receptors (8). In addition, XP-D/CS, but not XP-D, cells were unable to restart DHFR transcription after UV irradiation, due to Sirt1-mediated heterochromatinization of the promoter (11). Moreover, CSB is known to regulate RNAPI and RNAPII transcription (14,39).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that XPG forms a stable complex with TFIIH, to facilitate transactivation of nuclear receptors, and that XPG C-terminal truncation (deletion of amino acids 926 to 1186 [⌬926 -1186]) destabilizes the XPG-TFIIH complex, thereby reducing CAK-mediated phosphorylation and transactivation of nuclear receptors (8). In addition, NER factors are involved in the epigenetic regulation of gene expression (9)(10)(11)(12), indicating an important role in gene transcription. RNAPII-mediated transcription can be divided into three steps: initiation, elongation, and termination.…”
mentioning
confidence: 99%
“…These XPB and XPD mutations may prevent CAK module dissociation that is required for NER or could block normal function of other DNA repair factors to cause delayed transcriptional resumption (i.e. after DNA damage) commonly seen in XP/CS patients …”
Section: Pathologies Associated With Tfiih Functionmentioning
confidence: 99%